Implementasi Sistem Penjaminan Mutu Internal dan Eksternal dalam Meningkatkan Mutu Pembelajaran Perguruan Tinggi Indonesia - Sabran; Siti Julaiha (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
This article aims to analyze the extent to which the two quality assurance systems SPMI and SPME operate synergistically, as well as their effectiveness in improving the quality of higher education. The research adopts a library research approach, employing critical review techniques of primary literature, including accredited journal articles, institutional accreditation documents, and national regulations published between 2015 and 2025. The hypothesis proposed in this study states that the success of external accreditation is significantly influenced by the consistency and effectiveness of SPMI implementation at the institutional level. Findings indicate that SPMI has not been fully implemented in a systematic and sustainable manner, while SPME achievements often reflect administrative success rather than the actual strength of internal quality systems. This article offers a conceptual contribution by reinterpreting the relationship between SPMI and SPME as a two-way, evaluative, and reflective process. The results of this study are essential for strengthening strategies to develop a quality culture in higher education and for encouraging accreditation policies that are more contextual and substantive. In particular, the synergistic implementation of SPMI and SPME has direct implications for improving learning quality through enhanced continuous evaluation, curriculum refinement, and faculty professionalism.